Pengaruh Model Discovery Elerning terhadap Materi Sistem Pernapasan untuk Meningkatkan Kecerdasan Sosial Peserta Didik - Hartono, Adi; Tanjung, Indayana Febriani; Nurandi, Amelia Putri; Putri, Amelisa; Artika, Dewi Nurul; Efrillia, Celline; Armiati, Rika; Putri, Eka Wahyu (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2024)
Creative thinking must be developed in the learning process, so that students are accustomed to developing their creativity. According to Fadly (2014: 166) media is a component of learning resources or physical vehicles that contain instructional material among students which can stimulate students to learn. to convey messages or learning materials. In addition, learning media is useful for attracting students' interest in learning material and increasing student understanding. The goal is to apply an interesting and student-centered learning model with learning activities that activate students to construct subject matter so as to improve learning outcomes. One learning model that can overcome these problems is Discovery Learning. Discovery is a learning model that was developed based on a constructivism view. Keywords: Discovery Elerning Model, Respiratory System Material, Social Intelligence